Quantitative characterization of aluminosilicate gels in alkali-activated incineration bottom ash through sequential chemical extractions and deconvoluted nuclear magnetic resonance spectra - Zhu, Weiping (2021)
It has been reported that incineration bottom ash (IBA) from municipal solid waste can be a potential precursor for the synthesis of alkali-activated materials. It has been reported that the resulting alkali-activated IBA (AA-IBA) binder consists of 20 wt% calcium-containing phases. It is expected that aluminosilicate phases may coexist in the complex AA-IBA binder. Differentiating aluminosilicate phases from C-(A)-S-H phases could be challenging, for in general the two phases largely overlap in the spectra. In this study, aluminosilicate gels in a complex AA-IBA are separated and quantitatively characterized based on sequential chemical extractions, thermogravimetric analysis and nuclear magnetic resonance spectral subtraction and deconvolution. It concludes that the resulting AA-IBA binder consists of 17 wt% aluminosilicate gel with a Si/Al ratio of 2.52 resembling an aged alkali-activated coal fly ash. As understanding gel compositions in a binder is important, the methodology developed in this study is of significance and would benefit the development of alternative binders incorporating solid wastes and industry by-products.